Dual-citizenship as an instrument for the diaspora policy: The comparative analysis of Lithuania, Hungary and Poland - Anzhela Popyk (University of Warsaw, Centre of Migration Research (CMR), 2021)
The aim of this report is to present different types of dual citizenship regulations as a part of diaspora policy in three Central and Eastern European countries, Lithuania, Hungary and Poland. This paper presents an overview of current citizenship approaches and ways one can acquire or lose home state's citizenship. Besides, it presents the analysis of political, public and academic discourse on the process of introduction of dual citizenship to the states' diaspora, interior and foreign policies. The report ends with a comparative analysis of dual citizenship as a policy instrument in three chosen states.
Keywords: 330; dual citizenship; diaspora policy; Lithuania; Hungary; Poland